Nurse led shared care for patients on the waiting list for coronary artery bypass surgery: a randomised controlled trial. Issue 3 (1st September 2001) - McHugh, F; Lindsay, G M; Hanlon, P; Hutton, I; Brown, M R; Morrison, C; Wheatley, D J
Abstract : OBJECTIVE: To evaluate the effectiveness of a nurse led shared care programme to improve coronary heart disease risk factor levels and general health status and to reduce anxiety and depression in patients awaiting coronary artery bypass grafting (CABG). DESIGN: Randomised controlled trial. SETTING: Community, January 1997 to March 1998. STUDY GROUPS: 98 (75 male) consecutive patients were recruited to the study within one month of joining the waiting list for elective CABG at Glasgow Royal Infirmary University NHS Trust. Patients were randomly assigned to usual care (control; n = 49) or a nurse led intervention programme (n = 49). INTERVENTION: A shared care programme consisting of health education and motivational interviews, according to individual need, was carried out monthly. Care was provided in the patients' own homes by the community based cardiac liaison nurse alternating with the general practice nurse at the practice clinic. OUTCOME MEASURES: Smoking status, obesity, physical activity, anxiety and depression, general health status, and proportion of patients exceeding target values for blood pressure, plasma cholesterol, and alcohol intake. RESULTS: Compared with patients who received usual care, those participating in the nurse led programme were more likely to stop smoking (25% v 2%, p = 0.001) and to reduce obesity (body mass index > 30 kg/m 2 ) (16.3% v 8.1%, p = 0.01). Target systolic blood pressure improved by 19.8% compared with a 10.7% decrease in the control group (p = 0.001) and target diastolic blood pressure improved by 21.5% compared with 10.2% in the control group (p = 0.000). However, there was no significant difference between groups in the proportion of patients with cholesterol concentrations exceeding target values. There was a significant improvement in general health status scores across all eight domains of the 36 item short form health survey with changes in difference in mean scores between the groups ranging from 8.1 (p = 0.005) to 36.1 (p < 0.000). Levels of anxiety and depression improved (p < 0.000) and there was improvement in time spent being physically active (p < 0.000). CONCLUSIONS: This nurse led shared care intervention was shown to be effective for improving care for patients on the waiting list for CABG.